2018
DOI: 10.1371/journal.pone.0199158
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting serum concentration of vancomycin in critically ill oliguric pediatric patients receiving continuous venovenous hemodiafiltration

Abstract: Vancomycin is known to be unintentionally eliminated by continuous renal replacement therapy, and the protein bound fraction of vancomycin is also known to be different in adults and children. However, there are only a few studies investigating the relationship between the dose of continuous venovenous hemodiafiltration (CVVHDF) parameters and serum concentration of vancomycin in pediatric patients. The aim of this study was to determine clinical and demographic parameters that significantly affect serum vanco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(49 reference statements)
1
4
1
Order By: Relevance
“…A major factor impacting vancomycin trough concentration in our analysis was the weight-based vancomycin dose (mg/kg) similar to previous literature. 10 The current evaluation found that for each 1 mg/kg increase in vancomycin dose, the trough concentration increased by approximately 1 mcg/mL. In our study, 83% of patients receiving ≤10mg/ kg dose of vancomycin daily achieved a target trough goal, compared to only 47% of patients in higher dosage groups, with a median trough of 25.5 mg/mL in the higher-dose groups.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…A major factor impacting vancomycin trough concentration in our analysis was the weight-based vancomycin dose (mg/kg) similar to previous literature. 10 The current evaluation found that for each 1 mg/kg increase in vancomycin dose, the trough concentration increased by approximately 1 mcg/mL. In our study, 83% of patients receiving ≤10mg/ kg dose of vancomycin daily achieved a target trough goal, compared to only 47% of patients in higher dosage groups, with a median trough of 25.5 mg/mL in the higher-dose groups.…”
Section: Discussionsupporting
confidence: 42%
“…This result is similar to prior literature; however, in pediatric CVVHDF populations. 10,25 These findings are in contrast to Petejova et al, 30 who found no significant relationship between clearance of vancomycin and residual renal function in their 17 CVVH patients. It might be necessary to consider vancomycin dosage adjustment if renal function begins to recover and urine output improves.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Vancomycin clearance in critically ill patients receiving CRRT is reliably predicted by effluent flow rate. 23,94 Variability in the published literature for vancomycin exists regarding dosing recommendations needed to achieve target trough or AUC goals. Increasingly, AUC-targeted regimens are utilized, although precise dosing targets have not been studied and validated in a population requiring RRT.…”
Section: Continuous Renal Replacement Therapymentioning
confidence: 99%
“…CRRT-related clearance accounted for 63% of the total meropenem clearance in PICU patients [125]. For the frequently used antibiotics meropenem, piperacillin-tazobactam, and vancomycin, the effluent flow rate (net ultrafiltration + dialysate flow rate) appears to be the most reliable predictor of antibiotic clearance and should be taken into account when deciding on a dosing scheme [124,126]. In contrast with ECMO, most studies on antibiotic PK in CRRT have been performed in critically ill adults and some antibiotic dosing recommendations have been formulated for this population [124].…”
Section: Special Patient Populations In the Picu: Extracorporeal Circmentioning
confidence: 99%